Perencanaan Keuangan Syari’ah dalam Upaya Meningkatkan Kemampuan Manajemen Keungan Keluarga pada Anggota Majelis Ta’lim - Tri Aisyah (Peradaban: Jurnal Pengabdian Masyarakat, 2025)
The implementation of Sharia economics should not be solely focused on banking activities. Sharia economic systems are designed to benefit the broader economy, including family financial management. This concept aligns with the principles of various religions, particularly Islam, which is regarded as a blessing for all creation. This community service program aims to promote the application of Sharia economics in family financial management as an effort to improve household financial planning. The program draws lessons from mothers participating in learning activities held in the Belo village community forum (majelis). The program focuses on educating participants about Sharia-compliant financial principles, including budgeting, saving, debt management, and ethical spending. Through interactive sessions and discussions, the program seeks to raise awareness about the importance of incorporating Sharia values into daily financial practices. Participants are encouraged to adopt these principles to ensure financial discipline and align household financial management with Islamic teachings. The results of the program reveal a strong enthusiasm among participants to implement Sharia-compliant family financial planning. Many expressed a desire to immediately adopt these practices, reflecting a growing awareness of the importance of ethical financial management for household well-being. This initiative demonstrates that promoting Sharia economics at the household level can foster better financial planning and improve economic resilience in the community. It highlights the potential of community-based education programs to enhance financial literacy and support the broader adoption of Sharia economic principles in daily life.